Students' perception toward the use of TikTok video in learning writing descriptive text at MAN 1 Gresik - Syaifuddin Syaifuddin; Wiwik Muyassaroh Abdi; Alfufatin Nabilah; Dewi Larassati M.P; Fairuz Lazuwardiyyah (Universitas Islam Malang, 2021)
The purpose of this study was to explain the students' perception towards the use of TikTok in learning writing descriptive text. This analysis was a descriptive quantitative with a survey approach through questionnaire. The total of sample was 85 students at Islamic Senior High School of 1 Gresik especially from X MIPA 3, X MIPA 4, and X MIPA 5 in the 2020/2021 academic year. The information of this study was obtained through 15 questions adapted from Ilmiyah et al. & Ilmi. The researchers analyzed the data from questionnaire using SPSS 16 program to find out the descriptive statistical analysis. The finding captured that the interpretation of students regarding the use of TikTok in descriptive text of learning writing was positive. The students said they agreed with the use of TikTok in learning writing descriptive text due to it contributes positively and can foster the motivation of students. Furthermore, it makes the learners pay attention and participate in the learning process. Therefore, it is also recommended to students and teachers to use TikTok in order to create a contextual, relevant, and meaningful learning process, especially in writing descriptive text. They also allow students to participate in the learning process actively.